Ambient UVB Dose and Sun Enjoyment Are Important Predictors of Vitamin D Status in an Older Population. Issue 5 (22nd March 2017) - O'sullivan, Fiona; Laird, Eamon; Kelly, Dervla; van Geffen, Jos; van Weele, Michiel; McNulty, Helene; Hoey, Leane; Healy, Martin; McCarroll, Kevin; Cunningham, Conal; Casey, Miriam; Ward, Mary; et al.
Abstract: Background: UVB-induced skin synthesis is considered the key source of vitamin D, yet exposure to UVB is poorly accounted for in epidemiological studies. Objectives: The aim of this study was to examine the association of serum 25-hydroxyvitamin D [25(OH)D] concentration with accurately measured ambient UVB dose, sun enjoyment, supplements, and other factors. Methods: An all-Irish cohort of community-dwelling participants aged >60 y [median age: 73; 67% female; median 25(OH)D: 54.5 nmol/L] was used. Participants from this large, cross-sectional study completed a questionnaire to provide information on demographic factors and lifestyle (including supplement use and sun enjoyment). The Tropospheric Emission Monitoring Internet Service database was used to extract the daily ambient UVB dose at wavelengths that could induce vitamin D synthesis (D-UVB) over Ireland (latitude: 51°N–55°N). Blood sampling occurred throughout the year. Ambient exposure at the place of residence was calculated for each participant individually. Associations between determinants and serum 25(OH)D concentration were examined in a multivariate model. Random forest analysis was used to establish prediction models of vitamin D deficiency, and area under the curve (AUC) is shown. Results: In total, 5138 individuals were included. Median D-UVB was 63 mJ/cm 2, which varied between seasons and latitudes, despite the small latitude differential. Vitamin D supplementation (β = 27.7; P < 10 × 10 −10 ), D-UVB (β = 1.58 per 1000 mJ/cm 2 ; P < 10 × 10 −10 ), and sun enjoyment (β = 6.6; P < 0.001) were strongly positively associated with serum 25(OH)D. Those who avoided sunshine were largely at risk of deficiency (<40 nmol/L), whereas those who enjoyed sunshine tended to be vitamin D sufficient (≥50 nmol/L). D-UVB and sun enjoyment improved prediction of deficiency in non–supplement-taking individuals; the overall AUC improved by 3.5%. Conclusion: D-UVB and sun enjoyment are important predictors of vitamin D status, even in this elderly population at northern latitudes. Accurate estimation of ambient UVB can help to further clarify the role of other determinants of vitamin D status and inform sunshine recommendation guidelines.